(untitled) (Docentes 2.0 Journal, 2014)
It can be pointed out that the didactic aims to base and regulate the teaching-learning processes and in terms of pedagogy it is important to emphasize that it draws on the contributions of various sciences and disciplines, such as anthropology, psychology, philosophy, medicine and sociology, of this the utmost importance that a future teacher possesses knowledge as well as the educational curriculum as it is designed and developed, that is, it implies planning, programs to act, reflect and investigate on the practice itself, an exercise in autonomy and responsibility of the personal learning leading to the gradual professionalization of the student at the beginning of the teaching skills and actions.